The resonance frequency shift in an SOI nano-waveguide microring resonator - 臧俊斌 薛晨阳 韦丽萍 刘超 崔丹凤 王永华 张文栋 (Journal of semiconductors, 2013)
To research the effect of a deposited SiO2 insulating layer on the resonance frequency modulation of an SOI nanowaveguide ring cavity during integration fabrication, a rib waveguide ring resonator was systemati- cally designed and fabricated. SiO2 insulating layers with different thicknesses were deposited for analysis of the frequency shift characteristics. By testing the resonance transmission spectrum power of this structure, it is found that there are blue shifts after SiO2 deposition, and the frequency shift value of a structure with a 500 nm SiO2 insulating layer deposited is 0.8 nm, that is 0.24 THz at the resonance point where wavelength is around 1550 nm. Taking advantage of this conclusion, efficient optical modulation is available by choosing different frequency band resonance wavelengths to narrow the frequency modulation range.